GREEN TOURISM: NEW HORIZONS FOR THE ECONOMY OF KARAKALPAKSTAN (American Journal of Business Management, Economics and Banking, 2024)
This article explores the potential of green tourism as a sustainable economic development pathway for Karakalpakstan, a region in northwestern Uzbekistan known for its unique cultural heritage and ecological challenges, including the environmental degradation of the Aral Sea. Given the region's distinct landscape, biodiversity, and traditional lifestyle, green tourism presents an opportunity for economic growth while prioritizing environmental preservation. This paper discusses the current state of tourism in Karakalpakstan, the opportunities and challenges for developing green tourism, and strategies to promote sustainable travel in the region. Through a review of relevant case studies and global best practices, the study highlights how green tourism could stimulate local economies, create jobs, and raise awareness of environmental protection. The article concludes by recommending initiatives that could help Karakalpakstan become a model of sustainable tourism in Central Asia.